Into the great wide open: do alien plants spread from rivers to dry savanna in the Kruger National Park? - Petr Pyšek (NeoBiota, 2020)
Protected areas play an important role as refuges from invasive species impacts on biodiversity. Within the MOSAIK (Monitoring Savanna Biodiversity in the Kruger National Park) project, plant species were recorded in a representative set of 60 plots, 50 × 50 m in size, across the entire KNP, distributed so as to cover a range of savanna habitats, i.e. perennial rivers, seasonal rivers and dry crests, and two main bedrock types (granite and basalt). The data were used to assess the role of rivers in the dispersal of alien plants and study whether the alien plant species spread from rivers to open dry savanna. The resulting dataset provided the first thorough information on the spatial distribution of naturalised alien plants in KNP. In total, we recorded 20 plant species that are alien to the park, four of them considered invasive: Parthenium hysterophorus, Opuntia stricta, Xanthium strumarium and Zinnia peruviana. The most widespread species in KNP was Tridax procumbens, recorded in 11 plots (i.e. 18% of all sampled), four other species were found in > 10% of the plots. One species, Bidens bipinnata, was not previously reported from the park and represents a new record. The majority of aliens were concentrated along perennial rivers (60% of all occurrences), but some were repeatedly recorded at seasonal rivers as well and two of the most invasive species in KNP, Opuntia stricta and Parthenium hysterophorus, occurred also on dry crests away from water. The average number of alien species per plot was low (1.6), as was their mean percentage contribution to all species in a plot (2.2%), but some plots harboured as many as seven species and contributed up to 11.9%. Moreover, only 21 plots (35%) were alien-species free. In terms of the total species number per habitat, perennial rivers had significantly more aliens than crests and were marginally significantly richer than seasonal rivers. By recording all naturalised alien species occurring in the plots – many of them are not invasive but may become so in the future – and by using the GloNAF database of global distribution of naturalised species, we assessed the invasion potential of the recorded species.